The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pntd.0008566
|View full text |Cite
|
Sign up to set email alerts
|

A case for adoption of continuous albendazole treatment regimen for human echinococcal infections

Abstract: Cystic (CE) and alveolar (AE) echinococcosis are chronic, neglected parasitic diseases burdened by high morbidity and, for AE, by high mortality, if left untreated. CE and AE have a widespread distribution, including Europe. Albendazole (ABZ), a broad-spectrum benzimidazole drug widely used to treat parasitic infections, is the drug of choice for the management of CE and AE, and is parasitostatic on echinococcal metacestodes. In Europe, ABZ is licensed for interrupted “cyclic” treatment, for a maximum of 3 cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Cyclic dosing is considered inferior to continuous BMZ intake. While continuous intake, has never been officially approved by the Food and Drug Administration (FDA) or European Medicines Agency (EMA) it is now considered the gold standard of medical treatment by all experts [34]. Reuter et al presented their own experience with continuous and cyclic dosing and found no differences in toxicity [35] for which the drug was originally recommended to be interrupted every 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic dosing is considered inferior to continuous BMZ intake. While continuous intake, has never been officially approved by the Food and Drug Administration (FDA) or European Medicines Agency (EMA) it is now considered the gold standard of medical treatment by all experts [34]. Reuter et al presented their own experience with continuous and cyclic dosing and found no differences in toxicity [35] for which the drug was originally recommended to be interrupted every 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…In case of inextirpable AE lesion(s), albendazole (ABZ) will theoretically be given for life, sometimes in association with instrumental procedures. Continuous ABZ administration is superior to intermittent administration, 88,95 at a daily dose of 800 mg bid. Reduced doses are recommended in case of cholestasis and/or biliary cirrhosis, to avoid toxicity.…”
Section: Long-term Albendazole Therapymentioning
confidence: 95%
“…Such rates of hospi talisation from these three highly endemic countries suggests that sequelae and improper clinical manage ment might increase the disease burden of cystic echinococcosis. 18,38 Such morbidity should be taken in account for further research on the clinical burden of disease at the national level.…”
Section: Reviewmentioning
confidence: 99%